Multiple Drug Resistance Tuberculosis in Patients at TB Clinic Sisaket Hospital during 2005 - 2010 - เต็มเอี่ยม ทวีวุฒิ (Disease Control Journal, 2011)
Objective of this study were to assess the numbers, prevalence, result of treatment in MDR-TB cases and sensitivity test for TB drugs in TB-clinic Sisaket hospital. Retrospective study was done during October 1st 2005 to September 30th 2010. Analysis with descriptive statistic was used. It was found that there were 38 cases of MDR-TB in study period, 66% was male, average age was 44.8 years, non coinfection with HIV was 97.4%. Domicile outside responsibility subdistrict area was 81.6%. For prevalence of MDR-TB among new cases was 0.19% and prevalence among previously treated cases was 7.01%. Regarding to the sensitivity test for TB-drug, it was found that INH - resistancd 35 cases (92.1%), RFP -resistance 35 cases (92.1%), Streptomycin - resistance 22 cases (57.9%), ETB - resistance 16 cases (42.1%), PZA - resistance 1 case and ofloxacin - resistance 1 case. Result of treatment was as follow:success rate 76.3%, death rate 13.1%, during treatment 7.9% and transfer out 2.6%. Although the death rate was 13.1% but in the future if we could not reduce or control MDR-TB, extensively drug resistance Tuberculosis or XDR-TB would increase and would be more expensive and difficult to treat than MDR-TB.